Elucidating the Capabilities of Mirrorless Large Core Bundled Plastic Fiber Optic Displacement Sensor for Paracetamol Detection - Zulkifli, Mohd Zamani; Mohd Azri, Muhammad Fadhli; Mohd Yusof, Muhammad Khudhori; Shafiee, Saiful 'Arifin; Mohmad Sabere, Awis Sukarni; Yao, Lau Kuen; Samsudin, Sani Amril; Bahari, Muhammad Syahril; Yasin, Moh (2021)
A simple mirrorless plastic optical fiber displacement sensor was used to determine the concentration of paracetamol (PCM) in an aqueous solution. Paracetamol concentrations between 5 and 45 ppm were tested by the proposed sensor. With a mirror, the substantial sensitivity observed by an output power changed against displacement of 0.0403 mW/μm for the front slope and 0.023 mW/μm for the back slope with linearities of more than 99%. On the other hand, nonmirror reflector showed a sensitivity of 0.0006 mW/μm for the front slope and 0.0002 mW/μm for the back slope for the case of a red reflector and a sensitivity of 0.0007 mW/μm and 0.0003 mW/μm for the front and the back slope, respectively, for the case of a white reflector. The sensor sensitivity for the red and white coloured papers, which were used as the nonmirror reflectors and the mirror reflector itself against changing PCM concentrations, was 0.0004 mW/ppm, 0.0008 mW/ppm, and 0.02 mW/ppm, respectively. The experimental results indicated that the sensor was not only able to detect and measure the concentration of PCM in aqueous solutions but was also very stable with the additional advantages of a cost-effective and practical design that is highly beneficial for real-world sensing applications.